Answer:
![f(x)=-2x(x+4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/kjgygtpwm9jbn79yun50f0s0knhzdf57rw.png)
Explanation:
We want to find the equation of a quadratic function in factored form with zeros at x = -4 and x = 0 that passes through the point (-3, 6).
The factored form of a quadratic is given by:
![f(x)=a(x-p)(x-q)](https://img.qammunity.org/2022/formulas/mathematics/high-school/e0v9yib820dlq8vaktg70csb2zvhvj8xd4.png)
Where p and q are the zeros and a is the leading coefficient.
Since we have zeros at x = -4 and x = 0, let p = -4 and q = 0. Substitute:
![f(x)=a(x-(-4))(x-0)](https://img.qammunity.org/2022/formulas/mathematics/high-school/pdrd0rf5fgo6oq2guc0u38t7rnjmxv53yq.png)
Simplify:
![f(x)=ax(x+4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/et6kr236duq4txejdr5g29hh27etgxge7y.png)
And since we know that the function passes through the point (-3, 6), f(x) = 6 when x = -3. Thus:
![(6)=a(-3)(-3+4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/gu0c9ikfot37jr8xp1gdq5obx3xfel1rog.png)
Simplify:
![6=a(-3)(1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/w9ugn2euekaiypktp51iuhdgj27jwh0xh3.png)
Thus:
![-3a=6\Rightarrow a=-2](https://img.qammunity.org/2022/formulas/mathematics/high-school/iejubdr9v8vudm77j2ix43mybgvvlombj0.png)
So, our quadratic function is:
![f(x)=-2x(x+4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/kjgygtpwm9jbn79yun50f0s0knhzdf57rw.png)